(untitled) (Philological Studies, 2019)
In the article given the methods of poetic language investigation from the view of cognitive linguistics are represented. Technique in operation of poetic language studying makes it possible to reveal represented in them image of integral world fragment, due to description of contexts from the view of those conceptual criteria of extensions bring up to date through the text, therefore they are meaningful for poets who worked in different epochs and belonged to different literal schools. Work material analysis has showed that in some cases the snow image (as an important element of Russian fiction picture of the world) is given symbolic meaning. By way of some fiction texts examples those supplementary abstract meanings which ‘snow’ gains as the result of its aesthetic understanding not only as atmospheric precipitation but also as an entity.